A putative bHLH transcription factor is a candidate gene for male sterile 32, a locus affecting pollen and tapetum development in tomato. Issue 1 (21st July 2019) - Liu, Xiaoyan; Yang, Mengxia; Liu, Xiaolin; Wei, Kai; Cao, Xue; Wang, Xiaotian; Wang, Xiaoxuan; Guo, Yanmei; Du, Yongchen; Li, Junming; Liu, Lei; Shu, Jinshuai; et al.
Abstract: The tomato ( Solanum lycopersicum ) male sterile 32 ( ms32 ) mutant has been used in hybrid seed breeding programs largely because it produces no pollen and has exserted stigmas. In this study, histological examination of anthers revealed dysfunctional pollen and tapetum development in the ms32 mutant. The ms32 locus was fine mapped to a 28.5 kb interval that encoded four putative genes. Solyc01g081100, a homolog of Arabidopsis bHLH10/89/90 and rice EAT1, was proposed to be the candidate gene of MS32 because it contained a single nucleotide polymorphism (SNP) that led to the formation of a premature stop codon. A codominant derived cleaved amplified polymorphic sequence (dCAPS) marker, MS32D, was developed based on the SNP. Real-time quantitative reverse-transcription PCR showed that most of the genes, which were proposed to be involved in pollen and tapetum development in tomato, were downregulated in the ms32 mutant. These findings may aid in marker-assisted selection of ms32 in hybrid breeding programs and facilitate studies on the regulatory mechanisms of pollen and tapetum development in tomato.